Ungkapan Kepercayaan Rakyat Minangkabau di Parak Gadang Kecamatan Padang Timur - Atriyanti, Rini; Amir, Amril; Hamidin, Hamidin (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was to describe the form, meaning, structure, and function of the expression of the category of Minangkabau people in Padang District Parak Tower East. The data of study is a expression of the people who are in the Tower District Parak East Padang. The data source of this research is the speech of the informants about the expression of the people in Padang District Parak Tower East. Data were collected using interviews, records, and record. The findings of the study include the four issues, namely (1) the form of oral folklore and oral expressions of folklore in part the growing confidence of the people of Padang District Parak Tower East. (2) the meaning of an expression of the people who are in the Eastern District Parak Tower. (3) expression of the people’s trust tructure which consists of two parts, the first consisting of causation and the second consisting of signs, conventions. (4) categories kepercayaan expression and function of the people in Padang District East Tower Parak, class idiom about work, marriage, the human body, birth, travel, animals, folk medicine, housing, food, death, natural phenomena and function expression of ban, warned, entertain, educate.